RELAX (REducing Levels of AnXiety): a study protocol for a parallel two-arm randomised controlled trial evaluating a web-based early intervention for pregnant women with high levels of repetitive negative thinking to prevent escalating anxiety during pregnancy and after birth - Brittannia Volkmer; Yogini Sawjani; Mary Newburn; Jo Bennett; Megan McGovern; Laura Bridle; Nathalie Towner; Laura McCabe; Katherine Clark; Sophie Webster; Alison Hylton-Potts; Lucy Mayer; et al. (Trials)
Abstract Background Perinatal anxiety is common: up to 40% of pregnant women and new mothers experience high levels of anxiety. Given its prevalence, interventions that are low-intensity, highly accessible and cost-efficient, and target modifiable risk factors for anxiety are needed. Repetitive negative thinking (RNT)—such as worrying about ways things will go wrong in the future or ruminating about past negative events—is a risk factor for the development of anxiety. RNT is maintained by the tendency to generate negative interpretations of ambiguous situations. Methods A parallel two-arm randomised controlled trial will assess the efficacy of adding interpretation training (RELAX) to usual maternity care. Participants (N = 268) will be randomised to (i) 12 sessions of online interpretation training (RELAX) plus usual care, or (ii) usual care alone. We will assess anxiety, depression, RNT, and work and social adjustment at baseline, plus 4, 8 and 36 weeks later. Discussion Should the intervention result in lower levels of anxiety than usual care, it could be an accessible, cost-effective way to help women who are vulnerable to experiencing anxiety in the perinatal period. Trial registration ISRCTN 12754931. Registered 25th May 2023, prior to recruitment.